The 5′-end motif of Senecavirus A cDNA clone is genetically modified in 36 different ways for uncovering profiles of virus recovery - Meng, Hailan; Wang, Qi; Liu, Meiling; Li, Ziwei; Hao, Xiaojing; Zhao, Di; Dong, Yaqin; Liu, Shuang; Zhang, Feng; Cui, Jin; Ni, Bo; Shan, Hu; et al. (Frontiers in Microbiology, 2022)
Senecavirus A (SVA) is an emerging picornavirus. Its genome is one positive-sense, single-stranded RNA. The viral protein (VPg) is covalently linked to the extreme 5′ end of SVA genome. A complex hairpin-pseudoknot-hairpin (HPH) RNA structure was computationally predicted to form at the 5′ end of SVA genome. Three extra “U” residues (UUU) served as a linker between the HPH structure and the VPg, causing putative UUU-HPH formation at the extreme 5′ end of SVA genome. What the UUU-HPH structure functions as is unclear. One SVA cDNA clone (N0) was constructed previously in our laboratory. Here, the N0 was genetically tailored for reconstructing a set of 36 modified cDNA clones (N1 to N36) in an attempt to rescue replication-competent SVAs using reverse genetics. The results showed that a total of nine viruses were successfully recovered. Out of them, five were independently rescued from the N1 to N5, reconstructed by deleting the first five nucleotides (TTTGA) one by one from the extreme 5′ end of N0. Interestingly, these five viral progenies reverted back to the wild-type or/and wild-type-like genotype, suggesting SVA with an ability to repair nucleotide defects in its extreme 5′ end. The other four were independently rescued from the N26 to N29, containing different loop-modifying motifs in the first hairpin of HPH structure. These four loop-modifying motifs were genetically stable after serial passages, implying the wild-type loop motif was not a high-fidelity element in the first hairpin during SVA replication. The other genetically modified sequences were demonstrated to be lethal elements in the HPH structure for SVA recovery, suggesting that the putative HPH formation was a crucial cis-acting replication element for SVA propagation.